Three-dimensional analysis of condensation nanofluid film on an inclined rotating disk by efficient analytical methods. Issue 1 (2nd January 2018) - Hatami, M.; Jing, D.; Yousif, Majeed A.
Abstract: In this study, least square method (LSM) and differential transform method (DTM) applied to solve the three dimensional problem of steady nanofluid deposition on an inclined rotating disk is illustrated. The governing non-linear partial differential equations are reduced to the nonlinear ordinary differential equations system by similarity transform. There is a good agreement between the present analytical and numerical results. Results indicate that increasing nanofluid volume fraction leads to increase in temperature profile and highest temperature obtained for aluminium oxide (Al2 O3 )-water case.